The human corpse as an object of scientific research – complete freedom or regulation (Diametros, 2009)
The problematic of the article clearly differs from the majority of issues considered in this volume, since at the point at which experiments involving living specimens end there commences a new research area, experiments upon corpses. In common opinion the issue of such experiments seems to be marginal; however, it is worth scientific consideration since – as was said even in antiquity – the treatment of the bodies of the dead characterizes the sensibility of society toward the living. It might appear that “a corpse cannot be harmed”. Is this true, however? The final purpose of this article is to falsify this claim and to justify the necessity of formulating moral requirements upon experiments with human corpses.The realization of the above includes the following steps: defining the object of research, that is, the corpse, and establishing its ontological status, as well as a characterization of the area of research involving the bodies of the dead as an important scientific area. Next, the article presents by way of example one of the positions that opt for freedom of intervention in a dead body. In a response that draws upon personalism the author will establish the moral status of the human corpse together with essential ethical requirements regarding its use. At the end the above principles are applied to concrete areas of research.